Miscommunication in Arabic Fusha among Students with Different Teaching Approaches - Kirom, Abdul; Sokry, Bander Badri Mohammad; Qibtiyah, Luthfatul; Nurhayati, Dewi (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2025)
The integration of Arabic Fusḥa in school curricula is important for improving students’ language proficiency and communication skills across different educational contexts. However, differences in teaching approaches, environment exposure, and language environments can cause challenges, especially when students from different backgrounds try to communicate using the same language. These challenges may lead to misunderstanding and misinterpretation during interaction. The aim of this research is to analyze the causes of these communication problems by comparing the teaching methods of Arabic Fusḥa at Al-Amien Islamic Boarding School in Indonesia and Al-Hukama International School in Jeddah, and to identify the linguistic and non-linguistic factors that influence students’ communication outcomes. This research uses a comparative qualitative approach. The data were collected through online interaction via Google Meet involving five students from Al-Amien and three students from Al-Hukama, as well as face-to-face interviews with the students and their Arabic teachers. Additional data included teaching plans, materials, and schedules, and observations focusing on students’ daily use of Fusḥa inside and outside the classroom and school hours. The findings have shown clear differences. Al-Amien students, who mostly learn Classical Arabic, face difficulty adapting to Modern Standard Arabic, while Al-Hukama students receive more exposure to contemporary usage. These differences resulted in non-harmonic conversations and cases of miscommunication. The study suggests that balanced exposure to both forms of Arabic, supported by interactive cross-institutional activities, can improve mutual understanding and support more effective for Arabic Fusḥa communication.